Organic coffee production: mapping trends through bibliometric analysis - Gómez-Ortiz, Milton Marino; Vivares-Vergara, Jorge Andrés (Clío América, 2024)
Organic coffee (OC) cultivation, known for its environmental advantages and potential economic value, is this article’s focal point; because of the limited literature available, the objective is to pinpoint research trends in OC production to advance the sector’s socioeconomic development. A bibliometric analysis was conducted by searching Scopus and Web of Science, while the Tree of Science (ToS) algorithm was applied to reveal the field’s intellectual structure and current research trends, identifying a total of 360 scientific documents, reflecting a growing interest in various aspects of organic coffee; This article provides significant insights into the evolution of scientific production, the countries involved, prominent journals, authors, and their collaborative networks. Three key trends emerged: 1) Fair trade and gender equality, 2) Certifications and sustainability, and 3) Sustainable agroecological strategies. In conclusion, this study underscores the need for further research into various facets of organic coffee production, especially in countries where poverty alleviation and value creation are paramount.